PENERAPAN METODE BERCERITA DALAM MENINGKATKAN PENGETAHUAN BERPUASA ANAK USIA 5-6 TAHUN - Muhammad Rusydi Rasyid; Yusuf Tahir; Nurul Inayah; Dahlia Patiung; Ida Nurhidayat Thahir (Universitas Islam Negeri Alauddin Makassar, 2022)
Children Religious development, especially for children's knowledge about the virtues of fasting for Muslims, is very important to be stimulated because it becomes the basis for children to be able to know their religion. Through stories directly, it can stimulate children's development, especially about knowledge of the virtues of events for Muslims in the world. This study aims to determine the knowledge of knowing the age of child after the application of the storytelling method to children 5-6 years old. This community service research in the form of service learning was carried out at Aisyiyah Bustanul Athfal II Kindergarten Perumnas with a total of 4 children with 2 girls and 2 boys. The instruments used were picture paper, observation sheets for children and intervention implementation sheets. Data were analyzed using descriptive statistics. The results showed that children were able to increase their knowledge through storytelling activities. The findings in this study imply that the increase in knowledge of 2 girls is better than the increase in knowledge of 2 boys.